Table of Content - -, (Journal of engineering sciences and information technology, 2024)
Table of Content:1. Applying an ecosystem for the Development of Scientists, Sciences, and Sovereign Knowledge  to a National caseDr. AbdulHamid AbdulRahman Al-Abduljabbar , Dr. Bandar Abdullah Al-Saud2. Principles of Cloud Computing Infrastructure IaaSHousam Ghanim Alhazeem3. Exploring the Versatility of Aluminum in Mechanical EngineeringEng. Mohamed Ahmed Alawady4. Enhancing Cross-Age Facial Recognition with T2T-ViT Networks and Multi-Scale Attention DecompositionZakarya Mutahar Al-Haeer, Li Mengxia
Keywords: Journal of Engineering Sciences and Information Technology